Scribes and Demons: Literacy and Authority in a Capernaum Synagogue (Mark 1:21–28) - Elder, Nicholas A. (The catholic biblical quarterly, 2021)
This article argues that the watchers tradition influences Mark 1:21-28. Mark constructs the pericope as an intercalation that becomes intelligible once this demonological framework is registered. The central portion of the “sandwich” presents the content of Jesus’s teaching mentioned in the outer frames. Jesus’s didactic and exorcistic activity in the synagogue are one and the same. His teaching is “not like the scribes,” insofar as Jesus does not act as a text broker, mediating written traditions to the illiterate masses. Nor is his spiritual authority dependent on scribal attainments, as is the case with other Second Temple intermediaries, such as Enoch, Noah, and Solomon.